A Study of the Association between Serum Bone-Specific Alkaline Phosphatase and Serum Phosphorus Concentration or Dietary Phosphorus Intake - HOSOI, Takayuki; GOSEKI-SONE, Masae; HARAIKAWA, Mayu; KAWAMURA, Yuka; SUGIMOTO, Aoi; TANABE, Rieko; MICHIGAMI, Toshimi; SOGABE, Natsuko (Journal of Nutritional Science and Vitaminology, 2012)
Alkaline phosphatase (ALP) hydrolyzes a variety of monophosphate esters into phosphoric acid and alcohol at a high optimum pH (pH 8-10). Human ALPs are classified into four types: tissue-non specific (TNSALP, liver/bone/kidney), intestinal, placental, and germ cell types. Based on studies of hypophosphatasia (HPP), which is a systemic bone disease caused by the presence of either one or two pathologic mutations in ALPL that encodes TNSALP, TNSALP was suggested to be indispensable for skeletal mineralization. In this study, we explored the possibility that dietary nutrients contribute to regulate serum bone-specific ALP (BAP) activity. Serum biochemical parameters, such as serum ALP, BAP, osteocalcin, and fibroblast growth factor 23 (FGF23), were measured in healthy young subjects (n=193). Dietary nutrient intakes were measured based on 3-d food records before the day of blood examinations. The presence of a carrier of the deletion of T at nucleotide 1559 (c.1559delT), which has been reported to be the most frequent in Japanese HPP, was not detected in any subject. By the analysis of BAP activity and other biochemical parameters or dietary nutrient intakes, we obtained significant correlations between BAP activity and serum phosphorus (r=−0.165, p=0.022), calcium intake (mg/1,000 kcal/d) (r=−0.186, p=0.010), or phosphorus intake (mg/1,000 kcal/d) (r=−0.226, p=0.002). Further study on the regulation of BAP activity and calcium and/or phosphorus homeostasis will provide useful data for improving skeletal health.